Analysis and Monitoring of Small-Scale Rock Fracture Zone Deformation and Shaft Failure in a Metal Mine - Rong Lu; Fengshan Ma; Jie Zhao; Jianbo Wang; Guilin Li; Bing Dai (Advances in Civil Engineering)
Rock fracture zones were distributed in a metal mine, and their deformation was always neglected because they are available on a small scale. However, the deformation of the small-scale fracture zone may lead to serious consequences, such as underground building and structure failure. Combined with the ground movement and surface fissure monitoring, the deformation of several fracture zones was analyzed by field monitoring, experimental test, and numerical simulation. The results showed that fracture deformation promoted the surface fissure movement. The horizontal movement of the foot wall rock of the fracture was found to be larger than the hanging wall rock. Deep mining engineering resulted in the squeezing of the shallow fracture, and the shallow fracture deformed more severely than the deep fracture. In the study area, fracture zone displacements were estimated according to a numerical model. The deformation and stress comparison of the shallow fracture zone and the deep fracture zone provided the characteristic of the broken structure in the field investigation.